A Comparative Study to Check the Effectiveness of Task Oriented Activity on Walking Speed in Sub-Acute Stroke Patients: Life Sciences-Physiotherapy - K Shohe, Tokupu; Saikia Baruah, Trishna; Paul, Mantu; Dutta, Abhijit; kalita, Abhijit (International Journal of Life Science and Pharma Research, 2022)
Stroke which is also known as cerebrovascular accident (CVA) is a leading cause of impairment and disability in the world. There are many factors that affect the functional independence in post stroke people in which gait impairment plays a significant role. The purpose of stroke rehabilitation is to help patients to achieve as high level of functional independence as possible within their particular impairments. It is found that Task oriented activity has been shown to be an effective intervention to improve mobility. However, little is known about the impact of this intervention on the walking speed. The objective of study is to determine the combined effects of task oriented activity with conventional physiotherapy over conventional physiotherapy alone on walking speed in subjects with sub-acute stroke. This was a comparative study where pre and post design were used. Thirty (30) subjects with sub-acute stroke were taken considering the selection criteria; where Experimental group (Group-A) received task oriented activities and conventional physiotherapy and Control group (Group-B) received Conventional physiotherapy with 15 subjects in each group. Six minutes walk test (MWT) was used to assess the walking endurance and Functional ambulation categories (FAC) was used to evaluate the level of dependency of subjects in performing functional activities. Statistical analysis was done by using paired ‘t’ tests which showed significant improvement as the mean value of Group A (experimental group) mean 6MWT increase from -0.517 to -17.582, mean FAC increase from -1.288 to -3.055 but when intergroup analysis was done, its result was significant only in 6MWT were P= 0.046. task oriented activity after stroke could significantly improve walking endurance but not much significant on the level of dependency of the subject in performing functional activities.